Priority Control Strategy of VSC-MTDC System for Integrating Wind Power - Wen-ning Yan; Ke-jun Li; Zhuo-di Wang; Xin-han Meng; Jianguo Zhao (Journal of Electrical and Computer Engineering)
For the obvious advantages in integrating wind power, multiterminal HVDC transmission system (VSC-MTDC) is widely used. The priority control strategy is proposed in this paper considering the penetration rate of wind power for the AC grid. The strategy aims to solve the problems of power allocation and DC voltage control of the DC system. The main advantage of this strategy is that the demands for wind power of different areas can be satisfied and a power reference for the wind power trade can also be provided when wind farms transmit active power to several AC grids through the DC network. The objective is that power is well distributed according to the output power of wind farm with the demand of AC system and satisfactory control performance of DC voltage is obtained.